2016
DOI: 10.3390/ijms17091408
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as New Players in Cellular Senescence

Abstract: Cell senescence is associated with the secretion of many factors, the so-called “senescence-associated secretory phenotype”, which may alter tissue microenvironment, stimulating the organism to clean up senescent cells and replace them with newly divided ones. Therefore, although no longer dividing, these cells are still metabolically active and influence the surrounding tissue. Much attention has been recently focused not only on soluble factors released by senescent cells, but also on extracellular vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 92 publications
(96 reference statements)
0
91
0
Order By: Relevance
“…A large body of evidence shows that EVs, including exosomes and microvesicles, that are important mediators of intercellular communication, represent a key component of SASP . In general, EVs carry and transfer a wide variety of molecules, such as micro RNAs (miRNAs), messenger RNAs, DNA, and proteins.…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence shows that EVs, including exosomes and microvesicles, that are important mediators of intercellular communication, represent a key component of SASP . In general, EVs carry and transfer a wide variety of molecules, such as micro RNAs (miRNAs), messenger RNAs, DNA, and proteins.…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
“…A large body of evidence shows that EVs, including exosomes and microvesicles, that are important mediators of intercellular communication, represent a key component of SASP. 54,55 In general, EVs carry and transfer a wide variety of molecules, such as micro RNAs (miRNAs), messenger RNAs, DNA, and proteins. Remarkably, EVs secreted from senescent cells have unique characteristics and contribute to regulate the behavior of recipient cells similarly to soluble SASP factors.…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
“…Senescence is a complex cellular program induced by genotoxic, replicative, or oncogenic stress, in which cell-cyclearrested cells remain metabolically active and secrete several soluble factors, also known as the "senescence-associated secretory phenotype" (SASP), which mediates a variety of cellular responses, including modulation of cancer immune surveillance. Studies have shed a new light on the role of exosomes in mediating the cell-to-cell transmission of senescence signals, suggesting that exosomes may act as new components of the SASP (22).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was demonstrated that the functional hypothalamic stem/ progenitor cells release exosomes into the cerebral spinal fluid that likely contribute to slowing aging through transfer of miRNAs (57). Conversely, it has been demonstrated that senescent cells release more EVs and with a different composition (58)(59)(60), likely contributing to the SASP. Taken together, these results suggest that functional stem/ progenitor cell-derived EVs are able to extend healthspan and lifespan whereas senescent cell-derived EVs could function as pro-geronic factors.…”
Section: Evsmentioning
confidence: 99%